2015
DOI: 10.3390/en8066215
|View full text |Cite
|
Sign up to set email alerts
|

Finite Time Analysis of a Tri-Generation Cycle

Abstract: A review of the literature indicates that current tri-generation cycles show low thermal performance, even when optimised for maximum useful output. This paper presents a Finite Time analysis of a tri-generation cycle that is based upon coupled power and refrigeration Carnot cycles. The analysis applies equally well to Stirling cycles or any cycle that exhibits isothermal heat transfer with the environment and is internally reversible. It is shown that it is possible to obtain a significantly higher energy uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They found that the effects of heat transfer loss and variable specific heats of working fluid on the cycle performance were obvious. Agnew et al [12] presented a finite time analysis of a trigeneration cycle that was based upon coupled power and refrigeration Carnot cycles.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the effects of heat transfer loss and variable specific heats of working fluid on the cycle performance were obvious. Agnew et al [12] presented a finite time analysis of a trigeneration cycle that was based upon coupled power and refrigeration Carnot cycles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the nature of the cycle, the researched heat engine (HEG) cycles include steady flow cycles [32][33][34][35][36][37] and reciprocating cycles [38][39][40][41][42][43][44][45][46][47][48]. For the steady flow HEG cycle, considering the temperature change of the heat reservoir (HR) can make the cycle closer to the actual working state of the HEG, therefore, some scholars have studied the steady flow cycles with variable temperature HR [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%